Peningkatan Kualitas Produk Kopi melalui Introduksi Mesin Roasting pada UKM Kopi Blego Pak Mul Kabupaten Wonogiri - Isti Khomah; Kusnandar; Nuning Setyowati (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve product quality and foster product innovation in coffee processing through the introduction of coffee roasting technology and the development of drip bag coffee products for Blego Pak Mul Coffee MSME. The program was implemented through four stages: (1) program orientation and outreach, (2) introduction to and training in the use of a coffee roasting machine, (3) training in the production of drip bag coffee as a product diversification strategy, and (4) mentoring and evaluation. Program outcomes were analyzed using descriptive methods. The results demonstrated that the introduction of the coffee roasting machine improved coffee quality, as evidenced by more uniform bean color and superior aroma compared with the conventional manual roasting method. In addition, the drip bag coffee products featured more modern and practical packaging, thereby enhancing consumer appeal and increasing their market value potential. Overall, the program had a positive impact on strengthening the MSME's technical competencies, improving product quality, and fostering entrepreneurial capacity. These outcomes demonstrate the potential of appropriate technology and product innovation to enhance the competitiveness and sustainability of Blego Pak Mul Coffee MSME.